On Noncyclic Norm of Infinite Locally Finite Groups - Lukashova, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study relationships between the properties of a group and its noncyclic norm. We obtain a description of infinite locally finite groups whose noncyclic norms are non-Dedekind.